1996
DOI: 10.1113/jphysiol.1996.sp021415
|View full text |Cite
|
Sign up to set email alerts
|

Ca(2+)‐dependent non‐selective cation and potassium channels activated by bradykinin in pig coronary artery endothelial cells.

Abstract: 1. Using the cell-attached and inside-out modes of the patch-clamp technique, we studied the Ca2+-dependent ionic channels activated by bradykinin in cultured pig coronary artery endothelial cells to further understand electrophysiological events underlying cellular activation.2. In the cell-attached mode, bradykinin (94 nM) activated two types of Ca2P-dependent channels: a high conductance K+ channel (285 pS in high symmetrical K+), whose open state probability was increased by depolarization, and a lower con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
60
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 35 publications
5
60
1
Order By: Relevance
“…Most recently, cilostazol was shown to increase the outward K ϩ currents in SK-N-SH cells (human brain neuroblastoma cells) (Hong et al, 2003) by the opening of the maxi-K ϩ channels. On the other hand, the presence of BKCa channels has been shown in many types of endothelial cells (Rusko et al, 1992;Baron et al, 1996;Nilius et al, 1997), as well as in the EA.hy926 cell line (Haburcak et al, 1997). The maxi-K channel mRNA expression of the ␣-subunit, but not the ␤-subunit, was detected in the endothelium (Papassotiriou et al, 2000).…”
mentioning
confidence: 87%
“…Most recently, cilostazol was shown to increase the outward K ϩ currents in SK-N-SH cells (human brain neuroblastoma cells) (Hong et al, 2003) by the opening of the maxi-K ϩ channels. On the other hand, the presence of BKCa channels has been shown in many types of endothelial cells (Rusko et al, 1992;Baron et al, 1996;Nilius et al, 1997), as well as in the EA.hy926 cell line (Haburcak et al, 1997). The maxi-K channel mRNA expression of the ␣-subunit, but not the ␤-subunit, was detected in the endothelium (Papassotiriou et al, 2000).…”
mentioning
confidence: 87%
“…This hyperpolarization reaches a maximum close to the equilibrium potential of potassium ion when E K is changed by manipulating extracellular potassium concentration (Brunet & Be ny, 1989). In addition, whole cell and single channel patch clamp experiments showed that the kinins gate calcium-dependent potassium channels and that the transient current elicited by the peptides is a potassium current (Baron et al, 1996;1997). Therefore the stimulation of the endothelial cells by the kinins leads to the opening of potassium channels and consequently to a release of potassium ions.…”
Section: Source Of Endogenous Potassium Ionsmentioning
confidence: 99%
“…These rough estimates do not take into consideration the flexibility of d-tubocurarine and the channels. d-Tubocurarine is known to block large conductance Ca 2ϩ -and voltage-activated K ϩ channels (BKs) in micromolar concentrations from the cytoplasmic side (Egan et al, 1993;Baron et al, 1996). However, no data are available on d-tubocurarine binding to Kv channels.…”
mentioning
confidence: 99%